2020
DOI: 10.1371/journal.pone.0227999
|View full text |Cite
|
Sign up to set email alerts
|

Difference between physical therapist estimation and psychological patient-reported outcome measures in patients with low back pain

Abstract: Minimizing the number of patient-reported outcome measures (PROMs) can reduce patient burden. The primary aim of the present study was to investigate whether physical therapists (PTs) can estimate psychological PROM scores in patients with low back pain (LBP) through physical therapy evaluation. The secondary aims were; 1) to investigate whether the clinical experiences of PTs influence correlations between PT estimates and psychological PROM scores, and 2) to investigate the sensitivity and specificity of PT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 31 publications
1
27
1
Order By: Relevance
“…Although 37% of participants reported using formal screening tools, 51% of these participants indicated they used clinical judgement to guide when and with whom they were used, rather than routinely using screening tools with all patients. The interrater agreement between expert clinicians' clinical judgement for patient risk allocation and the risk allocation determined by the SBST has been shown to be "fair" (Hill et al, 2010;Miki et al, 2020). Therefore, this inconsistency in patient screening is of concern and shows that clinical judgement is probably not the best basis for deciding when/if to screen for psychosocial risk factors (Miki et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although 37% of participants reported using formal screening tools, 51% of these participants indicated they used clinical judgement to guide when and with whom they were used, rather than routinely using screening tools with all patients. The interrater agreement between expert clinicians' clinical judgement for patient risk allocation and the risk allocation determined by the SBST has been shown to be "fair" (Hill et al, 2010;Miki et al, 2020). Therefore, this inconsistency in patient screening is of concern and shows that clinical judgement is probably not the best basis for deciding when/if to screen for psychosocial risk factors (Miki et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The interrater agreement between expert clinicians' clinical judgement for patient risk allocation and the risk allocation determined by the SBST has been shown to be "fair" (Hill et al, 2010;Miki et al, 2020). Therefore, this inconsistency in patient screening is of concern and shows that clinical judgement is probably not the best basis for deciding when/if to screen for psychosocial risk factors (Miki et al, 2020). A systematic review of qualitative studies by Synnott et al (2015) found that although physiotherapists recognised psychosocial factors in LBP patients, they preferred to treat the mechanical aspects of LBP and may stigmatise people based on psychosocial factors.…”
Section: Discussionmentioning
confidence: 99%
“…Considering and appropriately addressing psychosocial barriers is a widely ac-cepted measure for successful management of low back pain (LBP) [1] [2] [3]. A study by Miki et al [4] included 78 patients with LBP and 21 physical therapists, and investigated whether the physical therapists could guess the scores of psychological Patient Reported Outcome Measures (PROMs) through physical therapy evaluation. The physical therapists could not guess the psychological PROM scores and the clinical experiences of the physical therapists did not enhance the accuracy of their guess.…”
Section: Introductionmentioning
confidence: 99%
“…However, another study [5] showed that trained physical therapists could guess patient anxiety through physical therapy evaluation. A potential reason for the discrepancy between the studies [4] [5] is the physical therapists' training level, and it was added to a research agenda to investigate whether certain post-graduate training programs might affect the ability of physical therapists to guess patient psychological PROM scores through physical therapy evaluation [4]. One promising post-graduate training program available around the world is the Mechanical Diagnosis and Therapy (MDT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation